Cognitive processing of verbal quantifiers in the context of affirmative and negative sentences: A Croatian study - Ćoso, Bojana; Bogunović, Irena (Research in Language, 2016)
Studies from English and German have found differences in the processing of affirmative and negative sentences. However, little attention has been given to quantifiers that form negations. A picture-sentence verification task was used to investigate the processing of different types of quantifiers in Croatian: universal quantifiers in affirmative sentences (e.g. all), non-universal quantifiers in compositional negations (e.g. not all), null quantifiers in negative concord (e.g. none) and relative disproportionate quantifiers in both affirmative and negative sentences (e.g. some). The results showed that non-universal and null quantifiers, as well as negations were processed significantly slower compared to affirmative sentences, which is in line with previous findings supporting the two-step model. The results also confirmed that more complex tasks require a longer reaction time. A significant difference in the processing of same-polarity sentences with first-order quantifiers was observed: sentences with null quantifiers were processed faster and more accurately than sentences with disproportional and non-universal quantifiers. A difference in reaction time was also found in affirmatives with different quantifiers: sentences with universal quantifiers were processed significantly faster and more accurately compared to sentences with relative disproportionate quantifiers. These findings indicate that the processing of quantifiers follows after the processing of affirmative information. In the context of the two-step model, the processing of quantifiers occurs in the second step, along with negations.